FILSAFAT PENDIDKAN DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Nur Firtri Annisa; Ariska Ainur Rahma (JOURNAL SAINS STUDENT RESEARCH, 2025)
The purpose of this study is to explain the ideas in the philosophy of education. The approach used is a literature review, in which information is collected from various sources, reviewed, and compiled. Using qualitative descriptive techniques, the findings of this study explain the ideas in the philosophy of education. The philosophy of Islamic education is described using descriptive techniques. Several scientific works used as primary references serve as data sources. The principles, ideas, and values that form the basis for planning and implementing education in an Islamic context are conceptually encompassed within the philosophy of education. Spiritual, moral, intellectual, and social elements are all integrated into the educational process from an Islamic perspective. Islamic philosophy of education encompasses a wide range of topics, including the educational environment and various educational issues. This technique considers spatial and geographical aspects, as well as the dimension of time. Therefore, the study of Islamic philosophy of education encompasses education at home, at school, and outside the classroom. The structure of educational institutions, educational management, and educational infrastructure are some of the themes that are the subject of this study. A deeper understanding of Islamic philosophy of education—which includes ontology, epistemology, and axioms—is expected to assist in building an educational system consistent with Islamic ideals.